2007
DOI: 10.1021/ic700830v
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Tetranuclear and Hexanuclear Palladium(II) Complexes and Their Host−guest Chemistry

Abstract: Cyclic tetrameric complexes have been prepared by the reaction of Pd(en)Cl 2 or Pd(dapol)Cl 2 , or their nitrato analogs, with Na 2 (5′GMP) in aqueous solution, where en = 1,2-diaminoethane, dapol = 1,3-diamino-2-propanol, 5′-GMP = guanosine 5′-monophosphate. Addition of certain small molecules containing hydrophobic groups resulted in the expansion of the tetramer to a cyclic hexamer with strong bonding of one guest per hexameric host. At pH 5-6, the guest molecule can be a cation, anion, or neutral, and thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…A similar multiplet has been observed previously in cyclic [Pd(en)(µ- N 1, N 7-5′-GMP)] n (n = 4 or 6) and was the result of rigidity in the en moiety due to the steric crowding around the Pd(II). 30 Since the 1:1 Pd(en)- 1,5-NAP complex is clearly monomeric, the reason for any steric crowding is unknown at this time. However, it is apparent that NO 3 − involvement must be important because it was not present when Pd(en)Cl 2 was used.…”
Section: Resultsmentioning
confidence: 99%
“…A similar multiplet has been observed previously in cyclic [Pd(en)(µ- N 1, N 7-5′-GMP)] n (n = 4 or 6) and was the result of rigidity in the en moiety due to the steric crowding around the Pd(II). 30 Since the 1:1 Pd(en)- 1,5-NAP complex is clearly monomeric, the reason for any steric crowding is unknown at this time. However, it is apparent that NO 3 − involvement must be important because it was not present when Pd(en)Cl 2 was used.…”
Section: Resultsmentioning
confidence: 99%
“…Since the N(10) position is protonated in water at neutral pH, it must be deprotonated for the Pd(II) complex to bond at this site, while bonding to the NH 2 groups does not require deprotonation. It is known that Pd(II) is capable of lowering the pK a of a proton by at least several pK units [33]. The data on DMSO solutions of [Pd(proflavineH)Cl 2 ](SO 4 ) 0.5 ·H 2 O showed that in this coordinating solvent the stability of the N(10)-bonded Pd structure, II , was slightly more stable than that of the NH 2 -bonded Pd structure.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to L21,t he steric disadvantage is minimisedi np yridylethynyl-based ligand L23,a nd hence, it is am uch better donort han that of cyanophenyl derivatives L22 a/b.T hus, the mixture of cis-[Pd(dppp)](OTf) 2 with ligands L22 b and L23 did not necessarily require the formation of ah eteroleptic complex in as pontaneous manner.I nstead,s elf-recognition occurred, leadingt oakinetic mixtureo fh omoleptic complexes [Pd 4 (dppp) 4 (L23) 2 ](OTf) 8 (27)a nd [Pd 4 (dppp) 4 (L22 b) 2 ](OTf) 8 (28). However,u pon heating am ixture of 27 and 28,achange could be observed.…”
Section: From Tetradentateligandsmentioning
confidence: 99%
“…However,t here are many homoleptic hexanuclear complexes of [(PdL') 6 (L) n ]c omposition. [24][25][26][27][28] Althoughc omplexes of [(PdL') 6 (L) 4 ]a re widely known, [24] other complexes,s uch as [(PdL') 6 (L)]-typet ubes, [25] [(PdL') 6 (L) 2 ]-type discs, [26] [(PdL') 6 (L) 3 ]-type tubes [27] and [(PdL') 6 (L) 6 ]-type hexagons, [28] are also known.H owever,h eteroligated hexanuclear assemblies with similar designs to those mentioned above are 6 (L a )(L b )] 2 -type [2]catenanes [29] and [(PdL') 6 (L a ) 2 (L b ) 4 ]-type [3]catenanes. [30] The complexation of cis-[Pd(en)(NO 3 ) 2 ]w ith am ixture of tripodal tridentate ligand L24 andf lat tridentate ligand L25 in a3 :1:1 stoichiometry under aqueous conditions resulted in catenane [Pd 3 (en) 3 (L26)(L27)] 2 (NO 3 ) 12 (30;F igure 12).…”
Section: From Tridentate Ligandsmentioning
confidence: 99%
See 1 more Smart Citation